Upshift : turning pressure into performance and crisis into creativity - Ramalingam, Ben (Flatiron Books, 2023)
"With over two decades' experience both observing and interpreting how people channel disaster into opportunity in the most extreme circumstances and environments on Earth, Ben Ramalingam has a unique vantage point from which to identify the key principles that can enable anyone to use stress as an opportunity for change. In Upshift, Ramalingam distils this expertise into an insightful, powerful, and engaging book that will show you how to reframe your set responses to stress and pressure and instead use them to harness the potential they hold not just for improving your work, your relationships, and your mindset, but for transforming them. Upshift takes readers on an epic journey from early humans' survival of the Ice Age to present times in our inescapable, pernicious and ever-shifting digital landscape. You will hear remarkable stories from a vast range of upshifters--all of whom carved new routes around perceived barriers using their powers to upshift. Underlying stories of how city commuters navigate train cancellations to how astronauts deal with life-threatening incidents, is one key message: We all have the power to innovate, whether or not we identify ourselves as creative or extraordinary. Maybe you're the challenger, who thrives by constructively disrupting the status quo like Greta Thunberg. Or perhaps you find yourself constantly tweaking, prodding, breaking, rebuilding, and improving like crafters such as the team that revolutionized space travel called the NASA Pirates. Do you love introducing people whose combined efforts will lead to greater achievements? You might be a connector, like master networker Ariana Huffington. In a runaway world that is an engine for perpetual crisis, Upshift is not only an essential toolkit for survival, it is a roadmap for positive, and potentially life-changing transformation and influence. You don't have to shut down - you can upshift"--